2019
DOI: 10.1097/ypg.0000000000000231
|View full text |Cite
|
Sign up to set email alerts
|

Zinc finger proteins in psychiatric disorders and response to psychotropic medications

Abstract: Zinc finger proteins are a large family of abundantly expressed small motifs that play a crucial role in a wide range of physiological and pathophysiological mechanisms. Findings published so far support an involvement of zinc fingers in psychiatric disorders. Most of the evidence has been provided for the zinc finger protein 804A (ZNF804A) gene, which has been suggested to be implicated in schizophrenia and bipolar disorder. This evidence has been corroborated by a wide range of functional studies showing tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…The functions of other members (NLRP8, -9, -11, -13) are still to be further investigated [18,22]. As is known, the zinc finger proteins (ZNFs) are the largest transcription factor family in human genome, which contain finger-like protrusions and play critical roles in physiological and pathophysiological mechanisms [26]. Previous research showed that duplications of zinc finger genes commonly occurred during the evolution [27].…”
Section: Discussionmentioning
confidence: 99%
“…The functions of other members (NLRP8, -9, -11, -13) are still to be further investigated [18,22]. As is known, the zinc finger proteins (ZNFs) are the largest transcription factor family in human genome, which contain finger-like protrusions and play critical roles in physiological and pathophysiological mechanisms [26]. Previous research showed that duplications of zinc finger genes commonly occurred during the evolution [27].…”
Section: Discussionmentioning
confidence: 99%
“…PPI of ZNF804A, ZFP82, TRIM58, SOX17, and C12orf42 analyzed by the STRING database. (Squassina et al, 2019). Previous research has revealed that zinc finger proteins exert significant effects on cancer progression (Jen and Wang, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It has a repeating structure of amino acid patterns, and cystines separated by a specific distance bind zinc fingers, which can interact with certain RNA/ DNA binding [30]. Due to its own structural characteristics, zinc finger protein can selectively bind to specific target structures, so that the gene expression of zinc finger protein plays an important role in the regulation of cell differentiation, embryo development and other life processes [31]. According to the different conserved domains of zinc finger proteins, they can be divided into C2H2, C4 and C6 [32].…”
Section: Discussionmentioning
confidence: 99%